The Glutamate Hypothesis: A Pathogenic Pathway from which Pharmacological Interventions have Emerged - Veerman, S. R. T.; Schulte, P. F. J.; de Haan, L. (Pharmacopsychiatry, 2014)
We discuss the relevance of the glutamate hypothesis in explaining cognitive disturbances and negative symptoms in schizophrenia. 4 lines of evidence support the hypothesis that glutamate deregulation, mainly through dysfunction of the N-methyl-D-aspartate (NMDA) receptor, is an important underlying mechanism of schizophrenia. Glutamate pathways are promising sites for intervention. Glutamate agonists combined with non-clozapine antipsychotics and glutamate antagonists augmented to clozapine show interesting clinical benefits in refractory schizophrenia. We illustrate how unique properties of the NMDA receptor antagonist memantine in addition to clozapine, may cause improvement of positive, negative and cognitive symptoms of schizophrenia.
Keywords: schizophrenia; glutamate; NMDA receptor; clozapine; glycine